Embedding Stakeholder Engagement into Sustainable Development Disclosure - Monteiro, Sónia (2024)
This chapter aims to explore the link between stakeholder engagement and corporate reporting by analyzing the regulatory framework on this topic provided by the Global Reporting Initiative (GRI), along with reviewing the scarce empirical literature on the impact of stakeholder engagement on SDG reporting.